Natural polymers - John, Maya J.; Thomas, Sabu (RSC green chemistry series, 2012)
Looks at the properties and characterization of cellulose, chitosan, furanic, starch, wool and silk nanocomposites and the potential industrial applications of natural polymer nanocomposites.